Hierarchical porous nickel oxide–carbon nanotubes as advanced pseudocapacitor materials for supercapacitors - Zhang, Xiang (2013)
Hierarchical porous carbon anode and metal oxide cathode are promising for supercapacitor with both high energy density and high power density. This Letter uses NiO and commercial carbon nanotubes (CNTs) as electrode materials for electrochemical capacitors with high energy storage capacities. Experimental results show that the specific capacitance of the electrode materials for 10%, 30% and 50% CNTs are 279, 242 and 112 F/g, respectively in an aqueous 1 M KOH electrolyte at a charge rate of 0.56 A/g. The maximum specific capacitance is 328 F/g at a charge rate of 0.33 A/g.